Functionalization of Cyclohexane Derivatives via Oxidative Radical Pathway - Teng, Fan; Cheng, Jiang (Chinese journal of chemistry, 2017)
The straightforward functionalization of simple alkanes (simple alkanes refer particularly to cyclohexane derivatives) has been a challenging subject in modern chemistry. However, with the development of oxidative radical reaction, it provided an available and alternative approach to meet the requirement of activating these compounds. In the review, we summarized the recent advances in this field, and the review mainly contained the following four parts: (1) the formation of C—C bonds; (2) the formation of C—N bonds; (3) the formation of C—S bonds and (4) the formation of C—O bonds. The straightforward functionalization of simple alkanes (simple alkanes refer particularly to cyclohexane derivatives) has been a challenging subject in modern chemistry. However, with the development of oxidative radical reaction, it provided an available and alternative approach to meet the requirement of activating these compounds. In the review, we summarized the recent advances in the field, and the review mainly contained the following four parts: (1) the formation of C—C bonds; (2) the formation of C—N bonds; (3) the formation of C—S bonds and (4) the formation of C—O bonds.